Influence of Motivation and Quality of Work Life on The Performance of Employees - Meithiana Indrasari; Mujtaba M Momin; Nur Syamsudin; Peter Newcombe; Surja Permana (STKIP Singkawang, 2018)
This examines the influence of motivation and quality of work life on employee performance CV. Prima Indo Tuna in Makassar. This type of research is explanatory attempt to explain the factors that affect the performance of the employees of the two factors, namely the motivation and the quality of working life. Respondents were 50 people who were employees at CV. Prima Indo Tuna Makassar on the processing or production either permanent or contract employee. Analysis of hypothesis verification regression analysis, which showed no significant influence between the variables of motivation and quality of work life on employee performance, it is proved by F count> 6,806 F table 3.20. From the analysis of the partial test proved that there is a significant influence on the variables of motivation and the quality of working life to the performance. Then the partial test results obtained by the partial determination coefficient (r2)of 0108 which shows motivation variable is the dominant variable affecting employee performance.